Fipronil and fipronil sulfone in chicken: From in vitro experiments to in vivo PBK model predictions. (July 2022) - Lautz, L.S.; Stoopen, G.; Ginting, A.J.; Hoogenboom, R.L.A.P.; Punt, A.
Abstract: In 2017 a large-scale fipronil contamination in eggs occurred in several European countries. Fipronil and its metabolites have the potential to be transferred into the eggs of laying hens, thereby entering the human food chain. Here, first the metabolism of fipronil was measured in vitro using chicken liver S9. The results show that fipronil is mainly metabolised into fipronil sulfone and the clearance obtained in vitro was extrapolated to in vivo liver clearance. In a second step a physiologically based kinetic model was developed with a focus on fipronil and its major sulfone metabolite and the model outcome was compared to available in vivo data in eggs from the literature. The experimentally obtained clearance was used as model input to evaluate whether such an in vitro -based model can be used in an early phase of a contamination incident to predict the time-concentration curves. Overall, all model predictions were within a 10-fold difference and the estimated elimination half-life for fipronil equivalents was 14 days. In vitro experiments are definitely recommended compared to in vivo studies, since they provide a fast first insight into the behaviour of a chemical in an organism. Highlights: Determination of in vitro metabolism of fipronil with chicken liver S9. Implementation of in vitro kinetic data in a PBK model for laying hens. Evaluation of fipronil predicted egg concentration with independent literature data. Improved model predictions when implementing literature information about the fraction absorbed of fipronil.